2020
DOI: 10.1111/cbdd.13779
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a novel peptide, Brevinin‐1H, from the skin secretion of Amolops hainanensis and rational design of several analogues

Abstract: As drug‐resistant bacteria have become a serious health problem and have caused thousands of deaths, finding new antibiotics has become an urgent research priority. A novel antimicrobial peptide, named Brevinin‐1H, was identified in the skin secretion of Amolops hainanensis through ‘shotgun’ cloning. It has broad‐spectrum antimicrobial activity against tested micro‐organisms and has anticancer cell activity. To improve its bioactivity and decrease its cytotoxicity, two structural analogues—Brevinin‐1Ha and Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Their hemolytic potential increased with increase in peptide concentration [10] . Generally, Brevinin peptides are hemolytic in nature [19] . Brevinin 1E, an antimicrobial peptide from the Ranidae family, has also shown severe hemolysis when added to human RBC at concentrations up to 100 μg/mL [20] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their hemolytic potential increased with increase in peptide concentration [10] . Generally, Brevinin peptides are hemolytic in nature [19] . Brevinin 1E, an antimicrobial peptide from the Ranidae family, has also shown severe hemolysis when added to human RBC at concentrations up to 100 μg/mL [20] .…”
Section: Resultsmentioning
confidence: 99%
“…[10] Generally, Brevinin peptides are hemolytic in nature. [19] Brevinin 1E, an antimicrobial peptide from the Ranidae family, has also shown severe hemolysis when added to human RBC at concentrations up to 100 μg/mL. [20] B1CTcu3 induced 2-60 percent lysis of RBCs in a concentration-dependent manner from 0.78 to 100 μM (S4 Appendix).…”
Section: Hemolytic Activitymentioning
confidence: 99%
“…AMPs exert their activity primarily by rupturing membranes and lysing bacterial cells [28,42,43]. It is reasonable to assume that its function in the early stage of ZIKV infection is to directly inactivate the virus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MIC of brevinin-1SPb and brevinin-1DYa against the growth of S. aureus was 13 µM and 32 µM with strong haemolysis [ 52 ]. On the other hand, by comparison with other brevinin-1 peptides, such as Ose [ 53 ], brevinin-1H [ 54 ], and B1A [ 55 ], B1OS-D-L showed comparable or even better antibacterial activity against Gram-positive bacteria with a lower level of haemolysis. Researchers have shown that the immune response of waxworms is quite similar to that of mammals [ 56 ].…”
Section: Discussionmentioning
confidence: 99%